Quantitative determination of amines used in post-combustion CO2 capture process by ion chromatography. (November 2015) - Fytianos, Georgios; Callot, Robin; Svendsen, Hallvard F.; Knuutila, Hanna K.
Highlights: Quantitative analysis of amines that are used in post-combustion CO2 capture. Method validation for all the amines. Method application at pilot plant. Abstract: In post-combustion CO2 capture (PCCC) with amine-based solvents, determining the amount of amine components present in the liquid phase is essential. The quantification of the solvent should be fast, accurate and simple. Toward this direction, suppressed cation exchange chromatography can be a powerful tool for the determination of the amines and their degradation products. In this paper, validated methods for 12 commercial amines and 2 degradation products were developed. The amines included primary, secondary and tertiary alkanolamines, polyamines as well as cyclic amines. Amines were determined with the chromatographic system Dionex Thermo Scientific ICS-5000 with CS19 as column and CG19 as guard column. A thermoscientific conductivity detector was used for identifying the various analytes. The validated methods were used for quantitative analysis and the coefficient of determination was greater than 0.99. Moreover, applications for determination of amines from pilot plant studies, trace analysis of cationic species and analysis of degraded samples are presented. Finally, it was shown that amine concentrations can be determined fast and accurate with CS19 without any special sample preparation.